Dynamic mislocalizations of nuclear pore complex proteins after focal cerebral ischemia in rat. Issue 9 (28th December 2016) - Li, Qian; Ohta, Yasuyuki; Yamashita, Toru; Shang, Jingwei; Deguchi, Kentaro; Feng, Tian; Sato, Kota; Hishikawa, Nozomi; Nakano, Yumiko; Abe, Koji
Abstract : Nuclear pore complexes (NPCs) play an important role in coordinating the transport of proteins and nucleic acids between the nucleus and cytoplasm, and are therefore essential for maintaining normal cellular function and liability. In the present study, we investigated the temporal immunohistochemical distribution of five representative components of NPCs—Ran GTPase‐activating protein 1 (RanGap1), glycoprotein‐210 (Gp210), nucleoporin 205 (Nup205), nucleoporin 107 (Nup107), and nucleoporin 50 (Nup50)—after 90 min of transient middle cerebral artery occlusion (tMCAO) up to 28 days after the reperfusion in rat brains. Single immunohistochemical analyses showed ring‐like stainings along the periphery of the nucleus in sham control brains. After tMCAO, Gp210 and Nup107 immunoreactivity continuously increased from 1 day, and RanGap1, Nup205, and Nup50 increased from 2 days until 28 days, which also displayed progressive precipitations within the nucleus in the peri‐ischemic area, while the ischemic core showed scarce expression with collapsed structure. Double immunofluorescent analyses revealed nuclear retention and apparent colocalization of RanGap1 with Nup205, Gp210 with Nup205, and partial colocalization of Nup205 with Nup107; most of the ischemic changes above were similar to those observed in patients with C9orf72‐genetic amyotrophic lateral sclerosis. Taken together, these observations suggest that the mislocalization of these nucleoporins may be a common pathogenesis of both ischemic and neurodegenerative disease. © 2016 Wiley Periodicals, Inc. Abstract : RanGap1 was clearly observed along the nuclear periphery in sham control brains. After tMCAO, RanGap1 immunoreactivity continuously increased in the peri‐ischemic area from 2 days until 28 days, which also displayed progressive precipitations within the nucleus in the peri‐ischemic area, while in the ischemic core, RanGap1 immunoreactivity was only weak.